2016
DOI: 10.2807/1560-7917.es.2016.21.42.30376
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged colonisation with Escherichia coli O25:ST131 versus other extended-spectrum beta-lactamase-producing E. coli in a long-term care facility with high endemic level of rectal colonisation, the Netherlands, 2013 to 2014

Abstract: The extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli clone ST131 (ESBL-ST131) has spread in healthcare settings worldwide. The reasons for its successful spread are unknown, but might include more effective transmission and/or longer persistence. We evaluated the colonisation dynamics of ESBL-producing E. coli (ESBL-EC), including ESBL-ST131, in a long-term care facility (LTCF) with an unusually high prevalence of rectal ESBL-EC colonisation. During a 14-month period, rectal or faecal samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 34 publications
5
42
0
1
Order By: Relevance
“…Our major contributors to phylogroups B2/D are ST131 (n = 33) and ST38 (n = 13). In a previous study, ST131 has been associated with prolonged carriage in a cohort of long term health care facility residents [18], while other studies, like the present, do not find this correlation [15,17]. Our observation support the notion that also other strains than ST131 have potential to colonise the human intestine for a long time.…”
Section: Discussionsupporting
confidence: 82%
“…Our major contributors to phylogroups B2/D are ST131 (n = 33) and ST38 (n = 13). In a previous study, ST131 has been associated with prolonged carriage in a cohort of long term health care facility residents [18], while other studies, like the present, do not find this correlation [15,17]. Our observation support the notion that also other strains than ST131 have potential to colonise the human intestine for a long time.…”
Section: Discussionsupporting
confidence: 82%
“…While we are unable to say for certain why the subjects in this study were colonized by ST131, studies have demonstrated high rates of colonization among people who have traveled to countries of endemicity or have stayed in long-term health care facilities and that CTX-M-containing ST131 clones have spread rapidly in the United States, where it is now a dominant lineage ( 35 , 38 41 ). Furthermore, ST131 is an efficient and prolonged colonizer, known to outcompete other resident strains and predicted to persist in the gastrointestinal tract for years ( 40 , 42 , 43 ), which may also help explain the readiness with which the resident E. coli population recovered following challenge and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The 6-year persistence of an ST131- H 30Rx strain in household 4 equals or exceeds previous persistence records for commensal E coli , ie, 6 years [ 38 ], 3.9 years ( ), and 3 years [ 17 ]. Some evidence supports that ST131- H 30 strains may persist longer than other antimicrobial-resistant E coli [ 39 ], possibly promoting the ST131 pandemic. It is notable that the core genome of household 4's ST131- H 30Rx strain was quite stable over 6 years, consistent with the low background mutation rate of E coli , including ST131 [ 17 , 40 ].…”
Section: Discussionmentioning
confidence: 99%